CULINARY HERITAGE OF KISALFÖLD IN HUNGARY - Kőmíves, Csaba (PEOPLE: International Journal of Social Sciences, 2017)
The study examines the landscape of one of the largest region in Western - Hungary, which has the most gastronomic roots. Based on the new trends of the traditional Hungarian cuisine, it is experiencing the creativity, the earlier consideration of flavours, following healthy diet and the appreciation of gastronomy. The empirical research (tasting dishes made by both the old and the new technologies) helps to highlight catering places special qualities and use of existence of the premium and quality products, such as eco-crafts or baby products, followed by the guests' need for new culinary experiences.